Safety Aspect of Enterococcus faecium FL31 Strain and Antibacterial Mechanism of Its Hydroxylated Bacteriocin BacFL31 against Listeria monocytogenes. (1st November 2018) - Chakchouk-Mtibaa, Ahlem; Sellem, Imen; Kamoun, Yosra; Smaoui, Slim; Karray-Rebai, Ines; Mellouli, Lotfi
Abstract : In previous work we have isolated and identified a new strain called Enterococcus faecium FL31. The active compound secreted by this strain, "BacFL31", has been purified and characterized. In the present study, safety aspect, assessed by microbiological and molecular tests, demonstrated that Enterococcus faecium FL31 was susceptible to relevant antibiotics, free of hemolytic, gelatinase, DNase, and lipase activities. In addition, it did not harbor virulence and antibiotic resistance genes. Combined SYTOX Green dye and UV-absorbing experiments, along with released extracellular potassium and transmembrane electrical potential measurements, showed that pure BacFL31 at a concentration of 1×MIC (50  μ g/mL) could damage cytoplasmic membrane of the pathogen Listeria monocytogenes ATCC19117. The same concentration causes the leakage of its intracellular constituents and leads to the destruction of this pathogenic microorganism. In summary, this work reflected characteristics of Enterococcus faecium FL31 strain and its bacteriocin in terms of functional and safety perspectives.